Alignment of Islamic banking sustainability indicators with sustainable development goals: policy recommendations for addressing the COVID-19 pandemic - Jan, Amin; Mata, Mario Nuno; Albinsson, Pia; Martins, Jose Moleiro; Hassan, Rusni; Mata, Pedro Neves (MDPI AG, 2021)
This study aims to establish the link of key Islamic banking sustainability indicators with the United Nations’ Sustainable Development Goals (UN SDGs) as a policy recommendation for sustainable development and to mitigate the distressing impacts of the COVID-19 pandemic on the triple bottom line (people, planet, and profit). To identify the key Islamic banking sustainability indicators, the authors selected the most cited sustainability measurement indexes in Islamic banking. Initially, the indexes were divided into 10 broader themes, and then the key Islamic banking sustainability indicators were shortlisted from each theme based on their high-frequency distribution. The shortlisted sustainability indicators were then ratified to be in line with Islamic philosophy based on “Maqasid al-Shariah” (objectives of Shariah) and were subsequently grouped into the three dimensions of economic, environmental, and social sustainability based on the axial coding method. Finally, the categorized sustainability indicators were aligned with the relevant UN SDGs through the axial coding method for policy formulation, and respectively 12 propositions were developed for policy formulation. This study labeled the methodological process of this study as the ECA method (exploration, categorization, alignment). The new ECA method offers a reverse extension in the “SDG compass” developed by the Global Reporting Initiative (GRI) for aligning business policies with the UN SDGs. The process of aligning Islamic banking sustainability indicators with the UN SDGs will provide a roadmap to recovery from the COVID-19 pandemic in terms of economic, environmental, and social issues. Due to the diversity of the UN SDG framework, it covers multiples aspects for sustainable development. Therefore, considering the UN SDGs in terms of various banking instruments will mitigate the multiple distressing impacts of COVID-19 on the triple bottom line (people, planet, and profit), it will also promote a sustainable development agenda